Pengaruh Kualitas Manajemen Sumber Daya Manusia dan Motivasi Kerja Terhadap Kinerja Pegawai padaDinas Pendidikan Kabupaten Tulungagung - Widyawati, Luziah; Baehaki, Imam (Universitas Islam Kadiri, 2024)
This research aims to: Analyzing the simultaneous influence of human resource quality work motivation on employee performance; analyzing the influence between human resource quality variables on employee performancee ; analyzing the influence between motivation variables on employee performance ; analyzing the most dominant influencee among human resource quality, work motivation variables on employee performance. This research uses Descriptive Quantitative. the population in this research is in the Education office employe of tulungagung Regency. The researcher does not specify a sample, because all members of the population will be examined. The technique is a method of data collection now. In this study, researchers used the software (software), Microsoft Office Excel 2007 to carry out a descriptive and statistical analysis software (software) Statistical Package for Social Sciences (SPSS) for Windows version 21.0 to carry out the test, test the classical, hypothesis testing and multiple linear regression analysis, , The research findings indicate a significant influence betwen the variables of human resource quality and motivation on employee performance .